Shree Birendra Hospital Chhauni Activities in the Year Poush 2059- Marga 2060 - KC, Bachchu Ram (Medical Journal of Shree Birendra Hospital, 2003)
Shree Birendra Hospital Chhauni Activities in the Year Poush 2059- Marga 2060